2017
DOI: 10.1007/s00394-017-1533-9
|View full text |Cite
|
Sign up to set email alerts
|

Plasma amino acids, adiposity, and weight change after gastric bypass surgery: are amino acids associated with weight regain?

Abstract: Plasma AAAs, BCAAs, and tCys at 2 years were associated with BMI at 2 years. In addition, plasma AAAs and BCAAs at 2 years were associated with weight loss from 0 to 2 years, while tCys at 2 years was associated with weight regain from 2 to 4 years after RYGB. These results suggest that high tCys at 2 years may be used as a prognostic marker for future weight regain. The study was registered in ClinicalTrials.gov (NCT0 1270451).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Clinical studies show that weight-loss surgeries reduce the levels of circulating BCAAs ( Hanvold et al, 2018 ; Laferrère et al, 2011 ; Magkos et al, 2013 ; Pakiet et al, 2020 ; Wijayatunga et al, 2018 ). We first determined whether the decrease in circulating BCAAs observed in humans is also observed in rodent models of VSG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies show that weight-loss surgeries reduce the levels of circulating BCAAs ( Hanvold et al, 2018 ; Laferrère et al, 2011 ; Magkos et al, 2013 ; Pakiet et al, 2020 ; Wijayatunga et al, 2018 ). We first determined whether the decrease in circulating BCAAs observed in humans is also observed in rodent models of VSG.…”
Section: Resultsmentioning
confidence: 99%
“…Although invasive, weight loss surgeries such as Roux-en-Y gastric bypass (RYGB) and vertical sleeve gastrectomy (VSG) have proven to be among the best treatments for weight loss and T2D ( Schauer et al, 2017 ). Recent studies also showed that bariatric surgery significantly reduces circulating BCAA levels post-surgery and BCAA levels remain lower at 2 years post-operatively ( Hanvold et al, 2018 ; Pakiet et al, 2020 ; Wijayatunga et al, 2018 ). These effective surgical interventions not only lead to decreased circulating BCAA levels but also have been shown to improve BCAA catabolism, specifically in adipose tissue ( Laferrère et al, 2011 ; She et al, 2007b ).…”
Section: Introductionmentioning
confidence: 97%
“…Numerous clinical studies have shown that bariatric surgery reduces the circulating BCAA levels (18)(19)(20)(21)28). The objective of our study was to answer whether improved BCAA homeostasis is necessary for the metabolic improvements after VSG.…”
Section: Discussionmentioning
confidence: 98%
“…Vertical Sleeve Gastrectomy (VSG), have proven to be among the best treatments for weight loss and T2D (17). Recent studies also showed that bariatric surgery significantly reduces circulating BCAA levels post-surgery and BCAA levels remain lower at 2 years post operatively (18)(19)(20). These effective surgical interventions not only lead to decreased circulating BCAA levels, but also have been shown to improve BCAA catabolism, specifically in adipose tissue (21,22).…”
Section: Although Invasive Weight Loss Surgeries Such As Roux-en-y Gmentioning
confidence: 99%
See 1 more Smart Citation